2022
DOI: 10.1021/acsomega.2c02062
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Geochemical Compositions of Ammonian Illite-Enriched High-Rank Coals of the Xingying Mine, Northeastern Chongqing, China

Abstract: Ammonian illite (NH 4 -illite)-rich late Permian coals of high rank were discovered in southwestern China. This research reports new mineralogical and geochemical data of 11 bench samples from the adjacent Xingying mine, northeastern Chongqing Coalfield, southwestern China, with an emphasis on the modes of occurrence and origin of NH 4 -illite. The Xingying coals, with low ash yields and medium sulfur, have a high rank (semianthrite, R o,ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Previous studies have also shown that the influence of hydrothermal solutions was the main cause of mineralogical and geochemical anomalies in Late Permian coals in Southwestern China [61,66,67]. Veined pyrite and layered calcite were observed in Jiashun coal (Figure 3d), providing evidence that the Jiashun coal was influenced by late hydrothermal fluids.…”
Section: Origin Of LI In the Jiashun Minementioning
confidence: 54%
“…Previous studies have also shown that the influence of hydrothermal solutions was the main cause of mineralogical and geochemical anomalies in Late Permian coals in Southwestern China [61,66,67]. Veined pyrite and layered calcite were observed in Jiashun coal (Figure 3d), providing evidence that the Jiashun coal was influenced by late hydrothermal fluids.…”
Section: Origin Of LI In the Jiashun Minementioning
confidence: 54%